PENGARUH E-WOM DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION DIMEDIASI OLEH BRAND TRUST - Respati, Ni Nyoman Rsi; Oktora Panasea, I Gede Nandya; Kharisma, Anak Agung Gita; Aditya, I Wayan Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p10, 2024)
The aim of this study is to analyze the impact of Electronic Word of Mouth (E-WOM) and Perceived Value, which includes Emotional Value, Social Value, Performance/Quality, and Price/Value for Money, on Purchase Intention. The study population consists of users of the Airbnb accommodation platform in Denpasar, with the sample comprising individuals who have completed at least high school education and have the intention to purchase accommodation products via the Airbnb platform. This research employs a purposive sampling method with 132 respondents, and the data were analyzed using descriptive methods and Partial Least Squares (PLS). Data collection was carried out using a Likert scale to measure the research indicators. The findings support the three proposed hypotheses: Perceived Value has a significant impact on Purchase Intention; Brand Trust mediates the effect of E-WOM on Purchase Intention; and Brand Trust also mediates the effect of Perceived Value on Purchase Intention. This study highlights the critical role of Brand Trust in influencing Purchase Intention, with three keys namely Brand Reliability, Brand Characteristics, and Company Characteristics.